Origins : God, Evolution, and the Question of the Cosmos - Kwok, Pui-lan (Book collections on Project MUSE., 2015)
Theological education, like theology itself, is becoming a truly a global enterprise. As such, theological education has to form, teach, and train leaders of faith communities prepared to lead in a transnational world. The teaching of theology with a global awareness has to wrestle with the nature and scope of the theological curriculum, teaching methods, and the context of learning. Teaching Global Theologies directly addresses both method and content by identifying local resources, successful pedagogies of inclusion, and best practices for teaching theology in a global context.